Socioeconomic Status in Relation to Stunting and Motor Skill Development of Toddlers in Urban and Rural Areas - Syihab, Syifa F; Stephani, Mesa Rahmi; Kumalasari, Isti; Suherman, Adang (KEMAS: Jurnal Kesehatan Masyarakat, 2021)
The development of child motor skills is closely related to nutritional status. Stunted children generally experience delays in motor development. The objective was to determine the relationship between stunting, socioeconomic status, and children’s motor skill development. This research was conducted in 2018 using a cross-sectional method. Respondents were 80 children aged 48-60 months in urban and rural areas of West Java. The researcher used a simple random technique data collection on anthropometric, socioeconomic, and motor skills development. Then it was analyzed using chi-square and Fisher exact methods. The researcher used a simple random technique data collection on anthropometric, socioeconomic, and motor skills development. Then it was analyzed using chi-square and Fisher exact methods. We found that stunting prevalence in rural areas was higher than in urban areas. As much as 30 % of children in rural areas and only 12.5 % of children in urban areas were categorized as stunted. There is no significant association between stunting with the family’s socioeconomic status and motor skill development. The weight for the age variable showed a significant association with stunting. Children who are malnourished have a stunting risk of 10.9 times greater than normal children (OR 10.9 p < 0.001).